Kombinasi Algoritma Rsa Dan Transposisi Sebagai Pengaman Data - Siagian, Herri (REMIK: Riset dan E-Jurnal Manajemen Informatika Komputer, 2016)
Information technology is growing has made it as the needs of both individuals, groups or companies, the security and confidentiality of the data becomes very important, so that the information can not be easily misused by parties who are not interested, therefore to secure messaging techniques required data security with steganography or cryptography, in steganographic techniques of data is converted into bits and inserted into digital media. The cryptographic techniques, the original message (plaintext) was converted into an encrypted message (ciphertext), in which to conduct the necessary encryption and decryption key. Algorithms transposition and Rivest Shamir Adleman (RSA) is a technique that can be used to perform encryption and decryption, by doing a combination of these techniques is expected to increase data security, so that unauthorized parties can not easily determine the message undisclosed